2022
DOI: 10.3389/fnins.2022.932384
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous excitatory neuron development in an isogenic cortical spheroid model of Down syndrome

Abstract: The intellectual disability (ID) in Down syndrome (DS) is thought to result from a variety of developmental deficits such as alterations in neural progenitor division, neurogenesis, gliogenesis, cortical architecture, and reduced cortical volume. However, the molecular processes underlying these neurodevelopmental changes are still elusive, preventing an understanding of the mechanistic basis of ID in DS. In this study, we used a pair of isogenic (trisomic and euploid) induced pluripotent stem cell (iPSC) line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 129 publications
4
16
0
Order By: Relevance
“…Individuals with DS have an 18% reduction in brain volume as compared to those without DS, and this decrease can be detected as early as the second trimester [ 8 , 204 , 205 ]. This is recapitulated in the iPSC-based three-dimensional models (organoids and spheroids), which show a decrease in the size of DS-derived cortical organoids [ 206 ] and in our own work utilizing cortical spheroids [ 207 ] as well as in the Ts65Dn mouse model [ 208 ]. It is noteworthy that in the mouse and human cerebellum, there is also a decrease in the number of granule and Purkinje cells [ 10 , 200 , 209 , 210 ].…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Individuals with DS have an 18% reduction in brain volume as compared to those without DS, and this decrease can be detected as early as the second trimester [ 8 , 204 , 205 ]. This is recapitulated in the iPSC-based three-dimensional models (organoids and spheroids), which show a decrease in the size of DS-derived cortical organoids [ 206 ] and in our own work utilizing cortical spheroids [ 207 ] as well as in the Ts65Dn mouse model [ 208 ]. It is noteworthy that in the mouse and human cerebellum, there is also a decrease in the number of granule and Purkinje cells [ 10 , 200 , 209 , 210 ].…”
Section: Introductionmentioning
confidence: 65%
“…Similarly, HSA21 genes DSCAM and DYRK1A have been implicated in the dysregulated neuronal migration and cortical lamination in DS [ 206 , 219 ]. Deficient neuronal motility and the dysregulation of the “roundabout” signaling pathway have been widely observed in DS [ 176 , 207 , 237 ]. Importantly, genes, such as ROBO2, ROBO4, and SLIT2 , which mediate neuronal migration and axon guidance, appear to be targeted by EZH2 and SUZ-12 [ 68 , 235 , 236 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes have been recapitulated recently in DS-derived three-dimensional cellular model organoids. Studies from our laboratory and others [ 33 , 35 ] demonstrated deficient detection of the neurons populating deep and superficial cortical layers in trisomic organoids. Furthermore, using single-cell transcriptomic studies, we found a particular vulnerability of trisomic excitatory neurons, transcriptomically corresponding to cortical layer IV [ 35 ], contributing further to the aberrant cortical development in DS.…”
Section: Introductionmentioning
confidence: 84%
“…In the current study, we used induced pluripotent stem cell (iPSC) isogenic lines derived from human patients with DS to generate cortical spheroids (CS) (or organoids) following a published protocol [ 58 ]. These CS contain several types of neural progenitor cells and excitatory neurons as well as inhibitory neurons, oligodendrocytes, and astrocytes [ 35 ] and recapitulate the developmental trajectory of an embryonic brain at mid-gestation [ 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%